2006
DOI: 10.1136/sti.2005.018093
|View full text |Cite
|
Sign up to set email alerts
|

One stop shop versus collaborative integration: what is the best way of delivering sexual health services?

Abstract: Objectives: To examine various models of integrated and/or one stop shop (OSS) sexual health services (including general practice, mainstream specialist services, and designated young people's services) and explore their relative strengths and weaknesses. Methods: Literature review and interviews with key informants involved in developing the National Strategy for Sexual Health and HIV (n = 11). Results: The paper focuses on five broad perspectives (logistics, public health, users, staff, and cost). Contracept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
34
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 22 publications
(16 reference statements)
1
34
0
Order By: Relevance
“…It is suggested that these new specialist services should be planned around patient need, and involve users in service design 8. New youth-orientated services are increasingly evident such as the ‘One-Stop Shop’,9 young people's ‘Help Centre’10 and sexual health clinics based in secondary schools 11. There has also been an extension of the services provided by community pharmacists, with the advent of emergency oral hormonal contraception (EHC) being available ‘over the counter’.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is suggested that these new specialist services should be planned around patient need, and involve users in service design 8. New youth-orientated services are increasingly evident such as the ‘One-Stop Shop’,9 young people's ‘Help Centre’10 and sexual health clinics based in secondary schools 11. There has also been an extension of the services provided by community pharmacists, with the advent of emergency oral hormonal contraception (EHC) being available ‘over the counter’.…”
Section: Introductionmentioning
confidence: 99%
“…It has been highlighted that there are challenges associated with user involvement in service planning and delivery; such as the need to ensure representation from a wide variety of backgrounds, and support for their participation 16. French et al 9 have suggested that more evidence is required on the impact and appropriateness of different service delivery models for young people.…”
Section: Introductionmentioning
confidence: 99%
“…Varying degrees of collaboration and integration between services have evolved to improve access to a full range of sexual health services 5 6. A one-stop shop is one example and in its broadest sense refers to the provision of sexual health services (usually, but not always limited to GUM and contraceptive clinics) on a single site.…”
mentioning
confidence: 99%
“…This is particularly important for general practice, given that evidence suggest that it has an important role to play in sexual health service provision, as well as the fact that one of the goals of the National Strategy for Sexual Health and HIV (Department of Health, 2001) is increasing the role of general practice in the management of sexual health. Additionally, while there is some agreement that one-stop shops might be a way of ensuring integration, there is less agreement about what such a service should look like (French et al, 2006), or where these services would be best located, for example in GUM clinics, walk-in centres, hospitals, or general practice. Developing a population-level understanding of service use and preference could help to address some of these questions.…”
mentioning
confidence: 99%
“…For example, community contraceptive clinics and genitourinary medicine (GUM) clinics that work collaboratively, but which do not provide integrated sexual health care on site (French et al, 2006). Also, while there is some evidence for increased user satisfaction with integrated services (Jones, 1996;Walsh, 1996;Bloxham et al, 1999;Hardon, 2003), there is currently little understanding of the effect that one-stop shop services will have on patterns of patient service use or preference at a population level.…”
mentioning
confidence: 99%